2015
DOI: 10.1007/s13762-015-0811-4
|View full text |Cite
|
Sign up to set email alerts
|

Electrosorption for organic pollutants removal and desalination by graphite and activated carbon fiber composite electrodes

Abstract: This paper investigates a new type of carbonbased electrodes, which were equipped with graphite and activated carbon fiber composite, to improve the performance of electrosorption. The results indicated that the highest desalination efficiency achieved 55 % and the optimal condition was 1.6 V voltage, 60 min retention time and 1.0 cm electrode distance. Freundlich isotherms successfully fitted with the respective behavior of the composite electrode and provided theoretical evidence for the desalination perform… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 51 publications
0
3
0
Order By: Relevance
“…For a long time, the development of the technology of capacitive deionization of water was constrained by the lack of materials with a sufficiently high developed inner surface. However, in recent decades (in the period from 1994 to 2021), with the development of technologies for the production of mesoporous carbons, materials with an active surface of 800-2,000 m 2 /g were created (for example, the design of aerogels at the Livermore National Laboratory), which are described in work [11], which led to the increased interest in the capacitive deionization of water.…”
Section: Literature Review and Problem Statementmentioning
confidence: 99%
“…For a long time, the development of the technology of capacitive deionization of water was constrained by the lack of materials with a sufficiently high developed inner surface. However, in recent decades (in the period from 1994 to 2021), with the development of technologies for the production of mesoporous carbons, materials with an active surface of 800-2,000 m 2 /g were created (for example, the design of aerogels at the Livermore National Laboratory), which are described in work [11], which led to the increased interest in the capacitive deionization of water.…”
Section: Literature Review and Problem Statementmentioning
confidence: 99%
“…Actually, a lot of research has been done to treat wastewater in the pharmaceutical industry and liquid waste from the pesticide industry, one of which is by the electrolysis method. Electrolysis methods such as those conducted by [7] using graphite and composite electrodes as electrodes to remove organic pollutants in the water medium and desalination of water [7]. Electrocoagulation methods have also been tried to reduce components of organic waste.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…Previous studies have shown that electrodes made of a carbonaceous material provide high efficiency in the degradation of pollutants. [22][23][24][25] There have been several studies in the literature reporting the used of graphite, 13,26,27 activated C fibres, [28][29][30][31][32] C felts [33][34][35] and C nanotubes 36,37 as anode in wastewater treatment (see Supporting information Table S1). Previously, Feng et al 38 provided in-depth analysis of carbonaceous electrode performance and its specific challenges in wastewater treatment applications.…”
Section: Introductionmentioning
confidence: 99%